Klarspråk virker! - Spets, Marte (Klart språk i Norden, 2014)
The Norwegian Public Roads Administration has documented the effect of rewriting letters in clear and concise language, and training the personnel in doing so. Every year, we at The Norwegian Public Roads Administration send out millions of letters to the Norwegian people. We realized that many of those receiving a letter simply did not understand its content, or what to do with the information provided in it. They needed help to understand, and contacted us. This resulted in us having an unnecessarily high number of cases where we responded to simple questions that the letters should have provided the answers for. What happened once we rewrote 10 of our standard letters and retrained our personnel? And what happened to the views of our 6,500 employees in the course of the plain language project? Over a period of time, The Norwegian Public Roads Administration has carried out four separate evaluations that show plain language works.